2006
DOI: 10.1160/th05-08-0534
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcus isolates from septic patients and healthy carriers differentially activate platelet signaling cascades

Abstract: Infection with group B streptococcus (GBS) is the most common cause of early onset neonatal sepsis in many countries, leading to neonatal morbidity and mortality. There is much evidence for a direct involvement of platelets in the pathogenesis of inflammation and sepsis. Several bacteria are known to directly interact with platelets leading to activation and aggregation, a phenomenon also observed with GBS. Here, we demonstrate that GBS rapidly bound to platelets; however, only strains isolated from septic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our own group could previously demonstrate that GBS is able to induce platelet aggregation [30]. In consequence, upregulated expression of HMOX-1 could reflect a protective mechanism against thrombotic complications after infection with GBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our own group could previously demonstrate that GBS is able to induce platelet aggregation [30]. In consequence, upregulated expression of HMOX-1 could reflect a protective mechanism against thrombotic complications after infection with GBS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of HMOX-1 might lead to elevated bilirubin levels [30], potentially interfering the change from fetal to adult hemoglobin [31]. Hyperbilirubinemia might be responsible for neurological long-term sequelae, observed after GBS newborn infections [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct interaction (Figure 1A) occurs when a bacterial adhesin binds directly to a platelet receptor [11,12]. An indirect interaction (Figure 1B) occurs when a bacterial adhesin binds to a plasma protein (or other soluble elements of the immune system such as immunoglobulins and complement proteins) which bridge the bacteria to a specific receptor on the platelet surface [11][12][13][14][15]. See Table 1 [16,17].…”
Section: Platelets Interactions With Bacteriamentioning
confidence: 99%
“…S agalactiae clinical isolates bearing FbsA elicit an FBG-dependent, specific aggregation of platelets, suggesting that FbsA may play an important role in thrombus formation and S. agalactiae -induced endocarditis ( 56 ). Notably, Siauw et al showed that septic GBS strains bind FBG, induce thromboxane synthesis and platelet aggregation, while colonizing GBS strains cause only shape change of platelets ( 91 ). Liu et al also found that strains of GBS isolated from septic arthritis can induce platelet aggregation and activation via the elevation of platelet Toll-like receptor 2 expression ( 92 ).…”
Section: Cwa Proteins Of S Agalactiaementioning
confidence: 99%